Draft Genome Sequences of Antimicrobial-Resistant Shigella Clinical Isolates from Pakistan - Lomonaco, Sara (Microbiol Resour Announc, 2019)
Shigella spp. are the most common cause of dysentery in developing countries and the second leading cause of diarrheal deaths worldwide. Multidrug-resistant (MDR) Shigella spp. are a serious threat to global health. Herein, we report draft genome sequences for three MDR Shigella isolates from Pakistan, two Shigella flexneri isolates and one Shigella sonnei isolate.